FUNCTIONAL STYLES IN ENGLISH LANGUAGE AND UZBEK LANGUAGE: A COMPARATIVE ANALYSIS - Qo’ziyeva Mubinaxon No’monjon qizi, (TADQIQOTLAR, 2026)
Abstract: This article examines the system of functional styles in the English and Uzbek  languages,  highlighting  their  similarities  and  differences.  Functional  styles reflect how language varies depending on communicative purpose, social context, and audience. The study focuses on five major styles in both languages: scientific, official, publicistic, literary, and colloquial. Through comparative analysis, the article identifies both  universal  and  language-  specific  features  shaped  by  cultural  and  linguistic traditions.The views of I.R. Galperin and I.V. Arnold on the classification of functional styles are outlined and compared. The article also presents the main characteristics of different styles and highlights their importance for effective communication.